2013
DOI: 10.1002/anie.201209288
|View full text |Cite
|
Sign up to set email alerts
|

Formyl Azide: Properties and Solid‐State Structure

Abstract: The simplest acyl azide, HC(O)N3, has been prepared as the neat substance and characterized by IR and Raman spectroscopy and low‐temperature X‐ray crystallography (see solid‐state structure; C white, H gray, N blue, O red). Photolysis of the azide in CO‐doped solid noble‐gas matrices furnished the first experimental proof of the elusive parent acyl isocyanate HC(O)NCO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 47 publications
(23 reference statements)
3
41
1
Order By: Relevance
“…52,53 As mentioned above, the closedshell configuration of 1 (II) is stabilized by an intramolecular O → N interaction, as indicated by the small OCN angle of 90.4°( Figure 5), a common structural feature found for other singlet carbonyl nitrenes. 54,55 In fact, formation of triplet carbonyl nitrenes by pyrolysis of the corresponding azides has been demonstrated for FC(O)N 3 56,57 and alkoxycarbonyl azides. 58,59 The PES for the decomposition of 3 (II) was studied using the same theoretical methods.…”
Section: Articlementioning
confidence: 99%
“…52,53 As mentioned above, the closedshell configuration of 1 (II) is stabilized by an intramolecular O → N interaction, as indicated by the small OCN angle of 90.4°( Figure 5), a common structural feature found for other singlet carbonyl nitrenes. 54,55 In fact, formation of triplet carbonyl nitrenes by pyrolysis of the corresponding azides has been demonstrated for FC(O)N 3 56,57 and alkoxycarbonyl azides. 58,59 The PES for the decomposition of 3 (II) was studied using the same theoretical methods.…”
Section: Articlementioning
confidence: 99%
“…This is similar to the case of the parent acyl azide HC(O)N 3 ,w here no nitrene but only HNCO wasf ound in as olid argonm atrix after photolysis with an ArF laser (l = 193 nm). [13] Indeed, quantum-chemical calculations on the potential energys urface( PES) of the decomposition of HC(O)N 3 supportt he preference of the concerted decomposition pathway,w ith the transition state of the stepwise decomposition to HC(O)N being higher in energy than that of the concerted route. [14] Recently,w eh ave shown that reactive a-oxo-nitrenes can be generated efficiently through the irradiation of a-oxo-azides with an ArF laser in solidn obleg as matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The (Figure 2A). The occurrence of the intense IR band at 2246.4 cm À1 ,w hich typicallyb elongs to the asymmetric NCO stretching vibrations in covalent isocyanates such as OSNCO (syn:2 230.6cm À1 , anti: 2237.6 cm À1 ,A rm atrix) [23] and HNCO (2259.6 cm À1 ,A rmatrix), [24] strongly indicates the formation of the CO-trapping product OPNCO. To aid the assignment, calculationso nt he IR spectrum of OPNCO in syn and anti conformations were performed at both CCSD(T)-F12/cc-pVTZ-F12 and B3LYP/6-311 + G(3df) levels ( Table 2).…”
mentioning
confidence: 99%